2016
DOI: 10.1186/s12873-017-0128-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome of severe ante-partum hemorrhage at the Teaching Hospital Yalgado Ouédraogo in Burkina Faso

Abstract: BackgroundHemorrhage is the main cause of maternal death during pregnancy. This study aims to evaluate incidence and outcomes of Severe Ante Partum Hemorrhage (SAPH) during the third trimester of pregnancy prior to delivery.MethodsAnalytical cross-sectional study with prospective data collection during 12 months in Yalgado Ouedraogo Hospital, Ouagadougou, Burkina Faso. In this context SAPH is specifically referring to Ante Partum Hemorrhage (APH) and Intra Partum Hemorrhage (IPH) in the 3rd trimester. Postpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
6
5
1
1
Order By: Relevance
“…The study conducted by Wasnik SK et al 2 found, rate of caesarean section was 90% in their APH group. In a similar study, reported by Lankoande M et al, 14 it was found rate of caesarean section in placenta praevia and abruptio placentae (i.e. retro placental hematoma) were 56.9%, 43.1% and vaginal birth in placenta praevia and abruptio placentae were 66.6%, 33.4% respectively.…”
Section: Discussionsupporting
confidence: 74%
“…The study conducted by Wasnik SK et al 2 found, rate of caesarean section was 90% in their APH group. In a similar study, reported by Lankoande M et al, 14 it was found rate of caesarean section in placenta praevia and abruptio placentae (i.e. retro placental hematoma) were 56.9%, 43.1% and vaginal birth in placenta praevia and abruptio placentae were 66.6%, 33.4% respectively.…”
Section: Discussionsupporting
confidence: 74%
“…This is because the placenta is the root of the fetus to suck nutrients from the mother in the form of O2, amino acids, vitamins, minerals and other substances to the fetus and remove the products of fetal metabolism and CO2. Impaired gas exchange in the placenta will cause fetal asphyxia [21][22] [23] The results of the study are in accordance with the theory put forward by Mochtar which states that placenta previa is a placenta that implants in the lower uterine segment and covers part or all of the internal uterine ostium. [6] The incidence of placenta previa is 0.4% -0.6%.…”
Section: Soekarjo Hospital Purwokertosupporting
confidence: 78%
“…Maternal mortality has regional variation, but, generally, it ranges from 5%-7% [12] and in spite of the fact that maternal mortality in sub-Saharan Africa accounts for two-thirds of the global maternal death rate, there was a significant reduction in the maternal mortality ratio (MMR) in north Africa and other parts of the world in the period from 2000 to 2017 [13]. A regional North African descriptive study, which involved 52 cases of major degree placenta previa, reported no maternal deaths and in another cross-sectional study conducted in West Africa, the maternal death rate was as high as 15.6% [14].…”
Section: Discussionmentioning
confidence: 99%